Beyond the Boundaries of Current Human Nature: Some Theological and Ethical Reflections on Transhumanism. Issue 1 (March 2015) - Childs, James M.
Abstract: Following a brief overview of the emerging transhumanist vision, Childs turns to a theological and ethical assessment. He recommends that there take place a community‐wide conversation over the prospects of a post‐human future that includes both nerds and theologians along with all stakeholders in a healthy human future. Christians should be guided by the eschatological values that inform love's commitment to the common good. How does the common commitment to justice take concrete shape in public policies governing the mounting advances in science and technology? How does the commitment to life and healing speak to the ethical distinction between the uses of biomedical technology for therapy versus for enhancement?